A Study Of Association Of Profits And Corporate Governance With Shareholders’ Value Of Nifty Companies In India – 2009-10 To 2019-20 - et. al., Dr. V. Y. John, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study undertakes to delve into the profit variants and proxies of corporate governance chosen, i.e., the composition of the Board of Directors and the shareholders to assess if there is a significant association of the above with the shareholders value of NIFTY Index, one of the prominent Stock Indices in India. The study also looks into the trends in the growth and contribution of various Industries comprising the NIFTY companies during the period of the study, 2009-10 to 2019-20 with the objective to identify industries which are contributing maximum value to shareholders. Results amazingly reveal that there is a significant association of the following profit variants, viz., Av. EAT(Earnings After Taxes), Av. CFO(Cash from Operations), Av. D/P(Dividend Pay-out) Ratio and Av. FCF(Free Cash Flows) with shareholder Value as measured by the metric, MVA (Market Value Added) of the NIFTY companies during the years 2009-10 to 2019-20. Results also reveal that there is no significant association between the composition of the Board of Directors and the shareholders to the MVA. Regression, Correlation, Bar and Line graphs were the tools used in analysing data. It is observed that the MV (Market Value/Capitalization) and more importantly MVA (Market Value Added) are relatively quite high and consistently increasing in case of companies under Banking and Financial Services, Software, FMCG(Fast Moving Consumer Goods) and Pharmaceutical Industry in India. These are followed by companies in the Infrastructure and Automobile Sectors.